1983
DOI: 10.1177/002199838301700507
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Photo-Degradation Behaviors of Glass-Fiber Reinforced Rigid Polyurethane Foam

Abstract: Thermal and photo-degradation of rigid polyurethane foams (PUF) and glass fiber reinforced rigid polyurethane foams (FRU) have been studied.It was found that FRU and PUF showed the nearly the same degradation behavior for flexural properties. In general, slightly higher degradation was observed with samples of lower expansion ratio, higher apparent density and containing glass fiber of shorter length.Measurement of interlaminar shear strength of heat-treated samples suggested that reduction in this property wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…or where k * = k S~ ^-1 and is termed the effective rate constant of bond strength loss. Similar assumptions have been made in an investigation of the heat-induced degradation of polymers, where the service lives of the polymers in question were also assessed on the basis of kinetic theory[10].In the form above, Equation (5b) describes a reaction where FM complexes are assumed to interact until no stable FM complexes remain, or the interfacial bond strength equals zero. However, it is suggested that it is more realistic to describe the interfacial bond as a collection or a spectrum of bond or complex types, each requiring a different amount of energy (activation energy) in order to interact with water.…”
mentioning
confidence: 99%
“…or where k * = k S~ ^-1 and is termed the effective rate constant of bond strength loss. Similar assumptions have been made in an investigation of the heat-induced degradation of polymers, where the service lives of the polymers in question were also assessed on the basis of kinetic theory[10].In the form above, Equation (5b) describes a reaction where FM complexes are assumed to interact until no stable FM complexes remain, or the interfacial bond strength equals zero. However, it is suggested that it is more realistic to describe the interfacial bond as a collection or a spectrum of bond or complex types, each requiring a different amount of energy (activation energy) in order to interact with water.…”
mentioning
confidence: 99%